(untitled) (Itinerarios Educativos, 2022)
Our concern for becoming free from authoritarian and oppressive models has brought us to the brink of extinguishing the very possibility of transmission, speech, listening, and attention. The inscription in culture through the introduction of the necessary limitations to open us to the world and protect us from the death drive begins to crumble before the mandate of short paths and the abandonment of everything that resists us. The search for immediate and unrestricted symbolic enjoyment undermines the possibility of sustaining processes of sublimation, calling into question the device of schooling and the ways created to transmit a relationship with culture. The mercantilist imperatives of flexibility, hyperactivity, and performance are articulated with the generalized questioning of the Law of Castration and drive narcissistic withdrawals that impact on intergenerational relationships, leading to the search for more horizontal relationships between parents and children. The school remains as one of the few institutions capable of safeguarding the human, protecting the asymmetry in the intergenerational bond and the relationship with culture. The issue is to glimpse some ways to safeguard formative processes, establishing a vital relationship with knowledge, the past, and what is necessary for the world not to fall apart.